Evolution of Ionizing Radiation Research 2015
DOI: 10.5772/60653
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Modification of Mouse Response to Total-Body-Irradiation

Abstract: Exposure to ionizing radiation (IR) could induce deleterious effects including cancer. Diet, as one of the major factors to influence susceptibility to many diseases, plays a critical role in maintaining human heath. It is known that unbalanced diet could result in health consequences, for example, high-calorie diet could lead to obesity, which could increase the risk of diabetes, heart disease, fatty liver, and some forms of cancer. Although the impact of diet on susceptibility to IR is thought to be big, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(98 reference statements)
1
1
0
Order By: Relevance
“…Our studies confirmed that there existed an interaction between life-style factors (i.e., high fat diet, low fat diet and alcohol drinking) and IR, which could lead to altered responses to IR in mice. 35 - 37 In the present work, combination of MDR and RAR was further verified in the mouse RAR model. Results indicated that MDR would not influence the phenotype of RAR measured as 30-day survival, and combined treatment with MDR and RAR could achieve a higher efficacy to relieve radiogenotoxicity and radiation-induced GI measured as reduced micronucleus frequency in the erythrocytes in the bone marrow.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our studies confirmed that there existed an interaction between life-style factors (i.e., high fat diet, low fat diet and alcohol drinking) and IR, which could lead to altered responses to IR in mice. 35 - 37 In the present work, combination of MDR and RAR was further verified in the mouse RAR model. Results indicated that MDR would not influence the phenotype of RAR measured as 30-day survival, and combined treatment with MDR and RAR could achieve a higher efficacy to relieve radiogenotoxicity and radiation-induced GI measured as reduced micronucleus frequency in the erythrocytes in the bone marrow.…”
Section: Discussionsupporting
confidence: 54%
“…Conversely, severe dietary restriction or malnutrition due to unbalanced diet could increase sensitivity of normal tissues to radiogenotoxicity, radiation-induced bone marrow death and life shortening in mice. 36 , 42 …”
Section: Discussionmentioning
confidence: 99%